Preparation method of Al-Mg-Sc-Zr alloy based on selective laser melting forming

By determining the optimal line energy density in laser selection melting technology and adjusting the laser power and scanning speed proportionally, the problem of low preparation efficiency of Al-Mg-Sc-Zr alloy workpieces is solved, and the workpiece preparation efficiency is significantly improved and performance is achieved Keep it.

CN119307761APending Publication Date: 2025-01-14JIANGLU MACHINERY & ELECTRONICS GROUP
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411411464.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, the workpiece printing preparation efficiency of Al-Mg-Sc-Zr alloys is not high and needs to be improved urgently.

Method used

By determining the optimal linear energy density of the alloy, the laser power and scanning speed proportionally change, ensuring that the workpiece molding quality remains unchanged, and improving the workpiece preparation efficiency. The specific steps include selecting Al-Mg alloy as the substrate, laying Al-Mg-Sc-Zr alloy powder, performing three-dimensional modeling and slicing processing, selecting the optimal line energy density when introducing the equipment, and not changing the thickness of the powder layer and scanning. In the case of spacing, adjust the laser power and scanning speed.

Benefits of technology

The preparation rate of Al-Mg-Sc-Zr alloy is significantly improved, while ensuring various performances of the workpiece, which reduces the time required to prepare the workpiece by 27% compared with the traditional method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307761A_ABST
    Figure CN119307761A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an Al-Mg-Sc-Zr alloy based on selective laser melting forming, and belongs to the technical field of additive manufacturing. Al-Mg alloy is selected as a base plate, and Al-Mg-Sc-Zr alloy powder is laid on the base plate; the method comprises the following steps of: performing three-dimensional modeling on to-be-processed metal construction, and slicing a model to prepare an STL file; an STL file is imported into equipment to prepare a workpiece, the optimal linear energy density is selected, the thickness of a powder laying layer and the scanning distance are not changed, the laser power and the scanning speed are proportionally changed, and tests show that the time required for preparing the workpiece by selecting the laser power of 440 W and the scanning speed of 1200 mm / s is shortened by 27% compared with the time required for preparing the workpiece by selecting the laser power of 220 W and the scanning speed of 600 mm / s. However, the forming quality and the mechanical property of the sample are not greatly changed, and the forming efficiency of a workpiece is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of additive manufacturing, and in particular to a method for preparing an Al-Mg-Sc-Zr alloy based on laser selective melting. Background Art

[0002] As one of the light metal materials, aluminum alloy has the characteristics of low density, good mechanical properties, good processing performance, easy recycling, excellent electrical and thermal conductivity, strong corrosion resistance, etc. It is widely used in the fields of shipbuilding, chemical industry, aerospace, transportation, etc. Rare earth elements Sc and Zr can inhibit the recrystallization of the alloy. By adding a small amount of Sc and Zr elements to aluminum alloy to prepare Al-Mg-Sc-Zr alloy, the grain size of aluminum alloy can be significantly refined and the mechanical properties of aluminum alloy can be improved.

[0003] Selective Laser Melting (SLM) is considered to be one of the most noteworthy additive manufacturing technologies. Compared with traditional casting and forging processes, it reduces the requirements for preparation technicians, and the parts prepared by it have more precise dimensions and more complex structures. It has the advantages of short processing and production cycle, high overall material utilization, manufacturability of complex parts, intelligent manufacturing, green environmental protection, high precision of prepared parts, and low degree of reprocessing. It breaks through the bottleneck of complex parts preparation and eliminates the limitations of traditional preparation. At the same time, the microstructure of the formed parts has a small grain size, high density, and uniform composition. It is superior to castings and forgings in mechanical properties. For the preparation field, it is a major technological breakthrough.

[0004] The SLM preparation of Al-Mg-Sc-Zr alloy has gradually matured, the process technology has gradually improved, and the performance of the prepared workpieces has been significantly improved compared with casting and other technologies. However, the efficiency of workpiece printing preparation is not high and urgently needs to be further improved. Summary of the invention

[0005] In view of the technical problems that the Al-Mg-Sc-Zr alloy samples prepared by the laser selective melting technology in the prior art have low efficiency in workpiece printing and preparation, the present invention provides a preparation method of the Al-Mg-Sc-Zr alloy based on laser selective melting, by determining the optimal linear energy density of the alloy and proportionally changing the values ​​of the laser power and the scanning speed, thereby achieving the goal of improving the workpiece preparation efficiency while ensuring various properties of the workpiece.

[0006] The technical solution adopted by the present invention to solve the above technical problems is as follows:

[0007] A method for preparing an Al-Mg-Sc-Zr alloy based on laser selective melting includes the following steps:

[0008] S1. Al-Mg alloy is selected as the substrate to prevent the workpiece from peeling off on the substrate surface due to alloys of different compositions; Al-Mg-Sc-Zr alloy powder is selected for spreading on the substrate, the particle size of the alloy powder is 20-63 μm, and the composition is: Mg 5.3-6.3wt.%, Sc 0.6-0.8wt.%, Zr 0.3-0.5wt.%, Mn 0.4-0.6wt.%, and the balance is Al.

[0009] S2. Three-dimensional modeling of the metal structure to be processed, slicing the model, and preparing an STL file;

[0010] S3. Import the STL file into the equipment to prepare the workpiece, select the optimal linear energy density, do not change the powder layer thickness and scanning interval, and proportionally change the laser power and scanning speed, so that there is no difference in the molding quality of the workpiece and the molding efficiency of the workpiece is improved.

[0011] Furthermore, in order to ensure the uniformity of the powder during the powder spreading process, the Al-Mg-Sc-Zr alloy powder is dried before use at a temperature of 80-100° C. for 3 to 5 hours.

[0012] Furthermore, the fluidity of the Al-Mg-Sc-Zr alloy powder is ≤130s / 50g, and the bulk density is ≥1g / cm 3 , thereby reducing the performance differences caused by raw materials.

[0013] It should be noted that, depending on the powder composition, the Al-based alloys currently used in the additive manufacturing direction are divided into AlSi7Mg, AlSi10Mg, Al-Mg-Sc-Zr and other alloys. Powders with different compositions have different requirements for laser energy density during the SLM preparation process, and the prepared workpieces are targeted at different locations and have different performances. Therefore, there are differences in the effect of improving the preparation rate of the alloy by proportionally changing the laser power and scanning speed.

[0014] Furthermore, the linear energy density is the ratio of laser power to scanning speed, and the optimal linear energy density is obtained through experimental testing. After a large number of experimental studies, the applicant finally selected the optimal linear energy density of 0.367 J / mm, the powder layer thickness of 0.03 mm, the scanning spacing of 0.13 mm, and the interlayer rotation angle of 67° in order to prepare a sample that meets the requirements of the present invention.

[0015] Furthermore, during the preparation of the workpiece, argon gas is filled into the printing chamber, and the oxygen content is less than 100 ppm.

[0016] Furthermore, during the preparation of the workpiece, the thickness of the first layer of powder should be reduced to less than 30 μm, and the first three layers of powder should be scanned using double laser exposure to improve the bonding between the alloy and the substrate and prevent the sample from collapsing during the preparation process.

[0017] Furthermore, the laser power is preferably 440 W, and the scanning speed is preferably 1200 mm / s.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] By adopting the method of the present invention to prepare Al-Mg-Sc-Zr alloy, the preparation rate of the alloy can be significantly improved by proportionally changing the laser power and the scanning speed, so that the relevant properties of the prepared Al-Mg-Sc-Zr alloy do not show obvious differences, while improving the workpiece preparation efficiency while ensuring various properties of the workpiece. The time required for preparing the workpiece using a laser power of 440 W and a scanning speed of 1200 mm / s is reduced by 27% compared with that using a laser power of 220 W and a scanning speed of 600 mm / s. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The morphology of the Al-Mg-Sc-Zr alloy powder melted by laser selective melting in the present invention;

[0021] Figure 2 These are the porosity test morphology images of the samples prepared by SLM in Examples 1, 2, and 3, wherein (a) is the sample in Example 1, (b) is the sample in Example 2, and (c) is the sample in Example 3;

[0022] Figure 3 It is a comparison chart of the tensile properties of Examples 1, 2, and 3. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited thereto.

[0024] Example 1

[0025] The preparation method of the laser selectively melted Al-Mg-Sc-Zr alloy in this embodiment is as follows:

[0026] (1) Al-Mg alloy is selected as the substrate to prevent the workpiece from peeling off on the substrate surface due to different alloy components; Al-Mg-Sc-Zr alloy powder is selected to be spread on the substrate. The particle size of the alloy powder is 30 μm, and the powder composition is: Mg 6.3wt.%, Sc 0.8wt.%, Zr 0.3wt.%, Mn 0.4wt.%, and the balance is Al. The powder is baked at 80°C for 5 hours. The powder morphology is as follows Figure 1 shown.

[0027] (2) Three-dimensional modeling of the metal structure to be processed is performed, and the model is sliced ​​to prepare an STL file.

[0028] (3) Import the STL file into the equipment, select the optimal linear energy density, do not change the powder layer thickness and scanning spacing, select the optimal linear energy density of 0.367 J / mm, the powder layer thickness of 0.03 mm, the scanning spacing of 0.13 mm, the interlayer rotation angle of 67°, the laser power of 440 W, and the scanning speed of 1200 mm / s to prepare Al-Mg-Sc-Zr alloy.

[0029] Observation of the prepared samples revealed that they had no obvious defects and had high surface accuracy.

[0030] Example 2

[0031] The preparation method of the laser selectively melted Al-Mg-Sc-Zr alloy in this embodiment is as follows:

[0032] (1) Al alloy is selected as the substrate to prevent the workpiece from peeling off on the substrate surface due to alloys of different compositions; Al-Mg-Sc-Zr alloy powder is selected to be spread on the substrate, the particle size of the alloy powder is 30 μm, and the powder composition is: Mg 6.3wt.%, Sc 0.8wt.%, Zr 0.3wt.%, Mn 0.4wt.%, and the balance is Al. The powder is baked at 80°C for 5 hours.

[0033] (2) Three-dimensional modeling of the metal structure to be processed is performed, and the model is sliced ​​to prepare an STL file.

[0034] (3) Import the STL file into the equipment, select the optimal linear energy density, do not change the powder layer thickness and scanning spacing, select the optimal linear energy density of 0.367 J / mm, the powder layer thickness of 0.03 mm, the scanning spacing of 0.13 mm, the interlayer rotation angle of 67°, the laser power of 330 W, and the scanning speed of 900 mm / s to prepare Al-Mg-Sc-Zr alloy.

[0035] Observation of the prepared samples revealed that they had no obvious defects and had high surface accuracy.

[0036] Example 3

[0037] The preparation method of the laser selectively melted Al-Mg-Sc-Zr alloy in this embodiment is as follows:

[0038] (1) Al alloy is selected as the substrate to prevent the workpiece from peeling off on the substrate surface due to alloys of different compositions; Al-Mg-Sc-Zr alloy powder is selected to be spread on the substrate, the particle size of the alloy powder is 30 μm, and the powder composition is: Mg 6.3wt.%, Sc 0.8wt.%, Zr 0.3wt.%, Mn 0.4wt.%, and the balance is Al. The powder is baked at 80°C for 5 hours.

[0039] (2) Three-dimensional modeling of the metal structure to be processed is performed, and the model is sliced ​​to prepare an STL file.

[0040] (3) Import the STL file into the equipment, select the optimal linear energy density, do not change the powder layer thickness and scanning spacing, select the optimal linear energy density of 0.367 J / mm, the powder layer thickness of 0.03 mm, the scanning spacing of 0.13 mm, the interlayer rotation angle of 67°, the laser power of 220 W, and the scanning speed of 600 mm / s to prepare Al-Mg-Sc-Zr alloy.

[0041] Observation of the prepared samples revealed that they had no obvious defects and had high surface accuracy.

[0042] The samples prepared in Examples 1, 2 and 3 were analyzed and tested:

[0043] 1. Take the SLM samples prepared in Examples 1, 2, and 3 and test the molding quality of the three samples. Polish the samples and observe the surface morphology of the samples using an optical microscope. Figure 2 As shown. It can be observed that the porosity of the samples in Examples 1, 2, and 3 is slightly different. At the same time, the relative density of the three samples was tested using the Archimedes drainage method, and the relative density of the samples in Examples 1, 2, and 3 was 99.09%, 98.80%, and 98.92%, respectively. This test data is consistent with the porosity test results.

[0044] 2. The mechanical properties of the SLM samples prepared in Examples 1, 2, and 3 were tested. The test results are as follows: Figure 3 By proportionally changing the laser power and scanning speed to prepare the sample, the tensile properties of the alloy did not change significantly, but the preparation time of Example 1 was reduced by 18% and 27% compared with that of Example 2 and Example 3, respectively. It can be seen that the preparation rate of the alloy can be significantly improved by increasing the laser power and scanning speed.

[0045] Comparative Example 1

[0046] The preparation method of the laser selectively melted Al-Mg-Sc-Zr alloy in this comparative example is as follows:

[0047] (1) Al alloy is selected as the substrate to prevent the workpiece from peeling off on the substrate surface due to different alloy components; Al-Mg-Sc-Zr alloy powder is selected with a particle size of 30 μm and a powder composition of Mg 6.3wt.%, Sc 0.8wt.%, Zr 0.3wt.%, Mn 0.4wt.%, and the balance is Al. The powder is baked at 80°C for 5 hours.

[0048] (2) Three-dimensional modeling of the metal structure to be processed is performed, and the model is sliced ​​to prepare an STL file.

[0049] (3) Import the STL file into the equipment, select the best linear energy density, do not change the powder layer thickness and scanning spacing, select the linear energy density of 0.413 J / mm, the powder layer thickness of 0.03 mm, the scanning spacing of 0.13 mm, the interlayer rotation angle of 67°, the laser power of 330 W, and the scanning speed of 700 mm / s to prepare Al-Mg-Sc-Zr alloy.

[0050] The prepared samples were tested and the relative density of the samples was 96.76%, which was significantly reduced.

[0051] Comparative Example 2

[0052] The Al-Mg-Sc-Zr alloy of this comparative example is prepared by laser selective melting as follows:

[0053] (1) Al alloy is selected as the substrate to prevent the workpiece from peeling off on the substrate surface due to different alloy components; Al-Mg-Sc-Zr alloy powder is selected with a particle size of 30 μm and a powder composition of Mg 6.3wt.%, Sc 0.8wt.%, Zr 0.3wt.%, Mn 0.4wt.%, and the balance is Al. The powder is baked at 80°C for 5 hours.

[0054] (2) Three-dimensional modeling of the metal structure to be processed is performed, and the model is sliced ​​to prepare an STL file.

[0055] (3) Import the STL file into the equipment, select the best linear energy density, do not change the powder layer thickness and scanning spacing, select the linear energy density of 0.330 J / mm, the powder layer thickness of 0.03 mm, the scanning spacing of 0.13 mm, the interlayer rotation angle of 67°, the laser power of 330 W, and the scanning speed of 1000 mm / s to prepare Al-Mg-Sc-Zr alloy.

[0056] The prepared sample was tested and the relative density of the sample was 96.05%, which was significantly reduced.

Claims

1. A method for preparing an Al-Mg-Sc-Zr alloy based on laser selective melting, characterized in that: The steps include: S1. Al-Mg alloy is selected as the substrate, and Al-Mg-Sc-Zr alloy powder is spread on the substrate. The particle size of the alloy powder is 20~63 μm, and the composition is: Mg 5.3~6.3 wt.%, Sc 0.6~0.8 wt.%, Zr 0.3~0.5 wt.%, Mn 0.4~0.6 wt.%, and the balance is Al; S2. Three-dimensional modeling of the metal structure to be processed, slicing the model, and preparing an STL file; S3. Import the STL file into the equipment to prepare the workpiece, select the optimal linear energy density, do not change the powder layer thickness and scanning interval, and proportionally change the laser power and scanning speed, so that there is no difference in the molding quality of the workpiece and the molding efficiency of the workpiece is improved.

2. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: The Al-Mg-Sc-Zr alloy powder is dried before use at a temperature of 80-100° C. for 3-5 hours.

3. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: The Al-Mg-Sc-Zr alloy powder has a fluidity of ≤130 s / 50g and a bulk density of ≥1 g / cm 3 .

4. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: The linear energy density is the ratio of laser power to scanning speed, and the optimal linear energy density is obtained through experimental testing.

5. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: The optimal linear energy density is 0.367 J / mm, the powder layer thickness is 0.03 mm, the scanning interval is 0.13 mm, and the interlayer rotation angle is set to 67°.

6. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: During the workpiece preparation process, the printing chamber is filled with argon gas and the oxygen content is less than 100 ppm.

7. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: During the workpiece preparation process, the thickness of the first layer of powder should be reduced to less than 30 μm, and the first three layers of powder should be scanned using double laser exposure.

8. The method for preparing Al-Mg-Sc-Zr alloy based on selective laser melting according to claim 1, characterized in that: The laser power is 440 W, and the scanning speed is 1200 mm / s.

Citation Information

Cited By

  • Method for reducing stress and cracking of high-strength aluminum alloy test piece formed by additive manufacturing through laser energy balance method

    CN119910198A